Athletic training and arrhythmogenic right ventricular cardiomyopathy - Alcobia Coelho, S.; Silva, F.; Silva, J.; António, N. (International Journal of Sports Medicine, 2019)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited cardiomyopathy characterized by ventricular arrhythmias and sudden death in the young and in competitive athletes. The deleterious role of exercise in the natural history of ARVC is clear. Even in the absence of a demonstrated arrhythmogenic substrate, family history or mutations of ARVC, intense physical exercise may in some individuals lead to the development of right ventricular dysfunction and arrhythmogenicity. This led to question the benignity of some adaptive features of the athlete's heart. In fact, there is an overlap between typical aspects of the athlete's heart and pathological changes described in ARVC, being challenging to distinguish the two conditions. The aim of this review is to highlight the aspects that help to distinguish between athlete's heart and ARVC, to review the major findings on exams helping in the differential diagnosis and to determine the implications on eligibility for leisure and competitive sports.